Detailed tail proteomic analysis of axolotl (Ambystoma mexicanum) using an mRNA‐seq reference database. Issue 1 (January 2017) - Demircan, Turan; Keskin, Ilknur; Dumlu, Seda Nilgün; Aytürk, Nilüfer; Avşaroğlu, Mahmut Erhan; Akgün, Emel; Öztürk, Gürkan; Baykal, Ahmet Tarık
Abstract : Salamander axolotl has been emerging as an important model for stem cell research due to its powerful regenerative capacity. Several advantages, such as the high capability of advanced tissue, organ, and appendages regeneration, promote axolotl as an ideal model system to extend our current understanding on the mechanisms of regeneration. Acknowledging the common molecular pathways between amphibians and mammals, there is a great potential to translate the messages from axolotl research to mammalian studies. However, the utilization of axolotl is hindered due to the lack of reference databases of genomic, transcriptomic, and proteomic data. Here, we introduce the proteome analysis of the axolotl tail section searched against an mRNA‐seq database. We translated axolotl mRNA sequences to protein sequences and annotated these to process the LC‐MS/MS data and identified 1001 nonredundant proteins. Functional classification of identified proteins was performed by gene ontology searches. The presence of some of the identified proteins was validated by in situ antibody labeling. Furthermore, we have analyzed the proteome expressional changes postamputation at three time points to evaluate the underlying mechanisms of the regeneration process. Taken together, this work expands the proteomics data of axolotl to contribute to its establishment as a fully utilized model.